What Drives Substantive Versus Symbolic Implementation of ISO 14001 in a Time of Economic Crisis? Insights from Greek Manufacturing Companies - Iatridis, Konstantinos (Journal of business ethics, 2018)
This paper analyses the role of external pressures, internal motivations and their interplay, with the intention of identifying whether they drive substantive or instead symbolic implementation of ISO 14001. The context is one of economic crisis. We focus on Greece, where the economic crisis has weakened the country’s institutional environment, and analyse qualitatively new interview data from 45 ISO 14001 certified firms. Our findings show that (a) weak external pressures can lead to a symbolic implementation of ISO 14001, as firms can defend their legitimacy without incurring the costs of internalization in the local market; (b) weak external pressures can lead to substantive implementation of ISO 14001 when firms have strong internal motivations seeking to strategically differentiate from competitors in international markets. Firms internalize ISO 14001 so as to restore their legitimacy and reputation in foreign markets and stimulate their competitiveness; and (c) strong internal motivations pave the way for companies to stimulate their competitiveness by enhancing their efficiency, as some companies might strengthen their position in the local market by implementing ISO 14001 substantively. The contribution of this paper to the literature on ISO 14001 internalization lies in refining existing theory on the importance of internal motivations for the substantive implementation of ISO 14001 in the context of economic crisis. In addition, this paper extends current theory by challenging studies that dismiss the importance of external pressures. We argue that the intensity of external pressures influences the internalization of ISO 14001, but propose that this relationship might not be linear.